Evaluation of the impact of the electrocardiogram course for licensed practical nurse (Research, Society and Development, 2023)
Introduction: The licensed practical nurses provide assistance to critically ill patients, therefore, requires knowledge about electrocardiographic tracing and its alterations. Studies show that there are gaps in the knowledge of registered nurses and licensed practical nurses about the electrocardiographic exam and continuing education is an important strategy to improve these professionals' knowledge. Objectives: To build and implement a remote course on electrocardiographic tracing for licensed practical nurses and to evaluate the professional's knowledge and performance before and after the course. Method: This is an exploratory-descriptive and educational intervention study, with a quantitative approach with a sample of 21 professionals who participated in the course from April to September 2022. Results: A modular course on electrocardiographic tracing was created, including pre- and post-course activities to assess the licensed practical nurses' knowledge, and there was a 7.2% improvement in knowledge in the post-course period. Conclusion: From the construction of the course and its implementation, there was an improvement in the knowledge of the licensed practical nurses, however, investments are needed for their participation in research, in the institutional infrastructure to enable the educational processes of licensed practical nurses mediated by technologies, considering its digital inclusion.